Effect of Socio-Personal Traits of Farmers on their Perception towards Social Media (Indian Journal of Extension Education, 2021)
Any progress in terms of utilization of a new ICT technology or innovation is greatly affected by how well it is perceived by the farmers. The perception of farmers is the product of their personal, social, psychological and economic background. Social media is one such new innovation which is spreading rapidly in rural areas and has transformed the communication process. The present study was conducted in Hisar and Sonipat districts of Haryana, with an objective to analyze the relationship between socio-personal traits of farmers with their perception towards social media. The data were collected personally from 200 respondents comprising 25 farmers from eight selected villages through a structured interview schedule. Findings revealed that 59 per cent of the farmers had neutral perception towards social media followed by 25.50 per cent farmers who had favourable perception. Further, analyses of the relationship between perception and profile of farmers revealed that, education, landholding, family income, cosmopoliteness-localiteness, mass media exposure, social participation, extension contact and extension participation were positively correlated with perception towards social media. It is recommended that there is a need to train farmers on better utilization of social media, use of social media marketing and sensitizing them about the positive aspects of social media.